Pengaruh Gaya Hidup dan Harga Terhadap Keputusan Pembelian (Studi Kasus Pada Onlineshop Pusathijabsyaree Surabaya) - Mariatus Sakdiyah (BIMA : Journal of Business and Innovation Management, 2021)
This study aims to determine what things should be improved and improved in targeting potential customer segments in terms of lifestyle which is then adjusted to the price at Pusathijabsyaree online shop surabaya. This research is a quantitative research with the method used is the associative method. The data obtained were obtained from distributing questionnaires to 98 respondents from online customers of Pusathijabsyaree online shop Surabaya by using saturated samples. The results of this study indicate that the lifestyle variable (X1) has no influence on the decision (Y) of purchasing at the online shop Pusathijabsyaree Surabaya. While the price variable (X2) has an influence on purchasing decisions (Y) at the online shop Pusathijabsyaree Surabaya. However, lifestyle variables (X1) and price (X2) together have an influence on purchasing decisions (Y) at the online shop Pusathijabsyaree Surabaya.